Richness and State of Knowledge of the Fauna of Yugoslavia: Lower Invertebrates (Metazoa: Invertebrata, ex. Insecta) - Boris Sket; Jože Bole; Adam Benović; Anton Brancelj; Janez Brglez; Marij Čuček; Božidar Ćurčić; Andrej Jaklin; Gordan Karman; Ivan Katavić; Mladen Kerovec; Ivan Kos; et al. (Acta Biologica Slovenica)
Approximately 3760 species from the discussed group are known from the Adriatic Sea, 4 could be endemic. Adriatic seems to harbour in fact 60-70% of all Mediterranean species. Approxi mately 5100 species and additional 1140 subspecies are known from continental habitats of Yugoslavia. Among terrestrial animals the richest are Aranea, Acarina, Gastropoda, among aquatic ones Rotatoria and Mollusca; the highest number of known parasitic species are in Digenea. Aquatic Oligochaeta comprise 80% of the European inventory, a number of some other groups 40-60 %. In Pseudoscor piones, Prosobranchia, Amphipoda, 80-90 % are endemics and so are 45-70 % of taxa in 6 following groups; the endemicity for the whole treated group is ca 25 %. The endemicity is nearly the same on the species and subspecies levels. The same is true for the percentage of troglobitic taxa, which is ca 20%. The Dinaride Region is far the richest in the world in the absolute number of stygobiotic taxa; this is even more prominent when counting the taxa density per area unit.